Chameleonic Behavior of the α‐Methylcyclopropyl Group and Its Through‐Space Interactions: A Route to Stabilized Three Redox States in Diarylnitroxides. Issue 30 (17th April 2020) - Levitskiy, Oleg A.; Dulov, Dmitry A.; Bogdanov, Alexey V.; Grishin, Yury K.; Nefedov, Sergey E.; Magdesieva, Tatiana V.
Abstract: The α‐methylcyclopropyl (MCP) group with conformationally dependent electronic properties is suggested as an additional structural "instrument" for stabilization of both open‐shell and ionic states of diarylnitroxides, to be used as "ambipolar" redox active materials. New MCP‐substituted diphenylnitroxides (fully characterized by electrochemical, spectral, and X‐ray data) are the most stable nitroxides of the diaryl type known to date [ τ 1/2 in benzene exceeds three months (2310 h)]. The radicals are capable to reversible oxidation and reduction, yielding stable oxoammonium cations and aminoxyl anions. DFT investigation of the electronic structure and geometry of the compounds confirmed the conformational switching of the cyclopropyl orientation relative to the adjacent aromatic π system is dependent on the nitroxide's redox state. Additional through‐space stabilizing interaction between the π‐acceptor orbital of the NO + moiety and the cyclopropyl "banana" bond orbital was also detected, highlighting its good hyperconjugative ability. The estimated σ ( para )MCP value (−0.32) confirms its strong electron‐donating properties. Abstract : Redox chameleons : First examples of nitroxide radicals containing α‐methylcyclopropyl (MCP) groups have been synthesized. Different orientations of the "chameleonic" MCP substituent relative to the phenyl ring are dependent on the redox state of the system, and through‐space hyperconjugative interactions provide enhanced stability of the radical, cationic, and anionic forms and open the possibility of the new nitroxides to be used as ambipolar redox‐active materials.